2007
DOI: 10.1093/aje/kwm053
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Retirement, and Changes in Physical Activity: Prospective Cohort Findings from the GLOBE Study

Abstract: There is increased recognition that determinants of health should be investigated in a life-course perspective. Retirement is a major transition in the life course and offers opportunities for changes in physical activity that may improve health in the aging population. The authors examined the effect of retirement on changes in physical activity in the GLOBE Study, a prospective cohort study known by the Dutch acronym for "Health and Living Conditions of the Population of Eindhoven and surroundings," 1991-200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 20 publications
5
119
0
4
Order By: Relevance
“…The influence of confounding from medical history should therefore be limited and the result thus compatible with a causal relationship between retirement and survival. One explanation behind this finding could be that retirement leads to adaptation of a less healthy lifestyle and this may increase the risk of CVD [9,10]. Notably, retirement was not associated with increased mortality in women in manual occupations.…”
Section: Discussionmentioning
confidence: 94%
“…The influence of confounding from medical history should therefore be limited and the result thus compatible with a causal relationship between retirement and survival. One explanation behind this finding could be that retirement leads to adaptation of a less healthy lifestyle and this may increase the risk of CVD [9,10]. Notably, retirement was not associated with increased mortality in women in manual occupations.…”
Section: Discussionmentioning
confidence: 94%
“…2,5,19,22,35]. Moreover, studies have also been conducted which deal with physical activity and ageing [14,50,52]. Dishman [18], for example, explores determinants of physical activity and exercise for persons of 65 years and older.…”
Section: Socio-economic Perspective On Physical Activitymentioning
confidence: 99%
“…However, it remains unclear whether age reflects the process of ageing, differences across birth cohorts or the impact of specific life-course transitions (16)(17)(18)(19) such as retirement. Studies on the transition to retirement have shown its positive impact on health outcomes such as self-rated health (20) and sleep (21) , but results are unclear regarding physical activity (22,23) or alcohol consumption (24) . In a cohort of 1200 Finnish civil servants, Helldán et al (25) found an increase in healthy food habits in retired women but not in retired men.…”
Section: Introductionmentioning
confidence: 99%